Mass actions in the context of pre-election campaigning - Шеверєва, В. Є. (Problems of legality, 2013)
The article considers the mass actions as a manifestation of political activity and form of campaigning. Analyzes of these forms of pre-election campaigning is conducted that can be attributed to mass actions, such as: meetings, marches, demonstrations, pickets, concerts, performances, sporting events, etc., in terms of the current legislation and the draft Law on Freedom of Assembly, with the participation of candidates for election. Own recommendations on the regulation of mass actions as a form of campaigning in the future law on such events have been proposed.